Hip adductor moment during gait in asymptomatic older adults - Vélez-Uribe, José David; Mejía-Uñates, Ana María; Piedrahita-Roldán, Sara Teresa; Ramírez-Estrada, Tatiana; Gómez-Suárez, Nicolás Eugenio; Duque-Ramírez, José Ricardo (Universidad y Salud, 2021)
Introduction: Although joint moment during waking has been associated with different clinical processes in the elderly population, there is a lack of reports in Colombia. Objective: To analyze the hip adductor moment during gait in asymptomatic older adults. Materials and methods: 110 participants were assessed using the VICON NEXUS 2.8.1. Full Body model software. 2 force platforms were used and the capture volume was delimited through 8 Bonita-10 optoelectronic cameras. Anthropometric, sociodemographic, spatiotemporal, and kinetic variables were included during the support phase, highlighting the two maximum peaks of the adductor moment. Results: The figures for Adductor Moment Peaks 1 and 2 (AMP1 and AMP2) were 0.76 and 0.70 Nm/Kg, respectively, which were related to mass, height and body mass index. Thus, a reference for the analysis of asymptomatic older adults was developed. Conclusion: The hip adductor moment graph is similar to that described by other researchers, but to a lesser extent than the values seen in coxarthrosis symptomatic population.